2021
DOI: 10.1136/sextrans-2020-054911
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis self-testing to expand test uptake among men who have sex with men: a theoretically informed mixed methods study in Zimbabwe

Abstract: ObjectivesSelf-testing for STIs such as HIV and syphilis may empower sexual minorities and expand uptake of STI testing. While much is known about HIV self-testing (HIVST), less is known about syphilis self-testing, particularly in low-income settings. The objective of this study is to determine context-specific facilitators and barriers for self-testing and to assess the usability of syphilis self-testing in Zimbabwe among men who have sex with men (MSM).MethodsThis mixed methods study was conducted in Harare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…However, the scoping review by Ong et al notes syphilis self-testing as a potential strategy to expand screening in key populations [ 117 ]. Since the initial search, studies in China and Zimbabwe have explored the role of syphilis self-testing in MSM [ 118 , 119 ], both of which noted the potential of self-testing to complement facility-based testing and facilitate testing of key populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the scoping review by Ong et al notes syphilis self-testing as a potential strategy to expand screening in key populations [ 117 ]. Since the initial search, studies in China and Zimbabwe have explored the role of syphilis self-testing in MSM [ 118 , 119 ], both of which noted the potential of self-testing to complement facility-based testing and facilitate testing of key populations.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed context-specific facilitators and barriers, and evaluated the usability of syphilis self-testing in MSM. 13 In our formative research, we found that MSM were willing to use self-test kits, and that this method provided privacy, convenience, autonomy, and reduced the potential for social and health care provider stigma. 13 There is extensive evidence on the effectiveness and acceptability of HIV self-testing in low-and middle-income countries, but data on syphilis selftesting are limited.…”
mentioning
confidence: 85%
“…13 In our formative research, we found that MSM were willing to use self-test kits, and that this method provided privacy, convenience, autonomy, and reduced the potential for social and health care provider stigma. 13 There is extensive evidence on the effectiveness and acceptability of HIV self-testing in low-and middle-income countries, but data on syphilis selftesting are limited. 14 As a result of this research gap, the World Health Organization has only given a conditional recommendation for the use of self-testing for syphilis diagnosis, even though it could potentially help to curb the syphilis epidemic in low-resource settings.…”
mentioning
confidence: 85%
“…How can digital STI services be used to enhance access to STI/HIV testing and what is their effectiveness? Digital technologies have been used to expand access to STI testing through self-sampling (e.g., HIV, syphilis, gonorrhea, chlamydia, human papillomavirus), (27)(28)(29) and self-testing (e.g., HIV,(30-32) syphilis, (33)(34)(35) and hepatitis C virus(36)). Digital tools cover a range of functions of varying degrees of complexity and sophistication, including booking appointments at STI clinics, ordering test kits , identifying people who would most benefit from testing (triaging), conducting online sexual health consultations, verifying completion of self-testing kits, referring people to access facility-based services, and provision of STI test results.…”
Section: Digital Sti Testingmentioning
confidence: 99%